To dare more boldly the audacious story of political risk - Hulsman, John C. 1967- (Princeton Princeton University Press, 2018)
Our baffling new multipolar world grows ever more complex, desperately calling for new ways of thinking, particularly when it comes to political risk. To Dare More Boldly provides those ways, telling the story of the rise of political risk analysis, both as a discipline and a lucrative high-stakes industry that guides the strategic decisions of corporations and governments around the world. It assesses why recent predictions have gone wrong and boldly puts forward ten analytical commandments that can stand the test of time. Written by one of the field's leading practitioners, this incisive book derives these indelible rules of the game from a wide-ranging and entertaining survey of world history. John Hulsman looks at examples as seemingly unconnected as the ancient Greeks and Romans, the Third Crusade, the Italian Renaissance, America's founders, Napoleon, the Battle of Gettysburg, the British Empire, the Kaiser's Germany, the breakup of the Beatles, Charles Manson, and Deng Xiaoping's China. Hulsman makes sense of yesterday's world, and in doing so provides an invaluable conceptual tool kit for navigating today's. To Dare More Boldly creatively explains why political risk analysis is vital for business and political leaders alike, and authoritatively establishes the analytical rules of thumb that practitioners need to do it effectively. - from book jacket.
1.480 BC: Introduction-The First Political Risk Analysis: The Pythia of Delphi -- 2.31 AD: We Are the Risk: The Decline and Fall of the Roman Empire -- 3. 1192 AD: Gaming Our Lunatics; The Assassins and the Old Man of the Mountain -- 4. 1503 AD: Gaming Out Chess Players; Machiavelli, Cesare Borgia, and Pope Julius II -- 5. 1776: Everything to Play For; John Adams and Game-Changers -- 6. 1797: Getting to Goldilocks; Napoleon and the Venetian Republic -- 7. 1863: The Losing Gambler Syndrome; Robert E. Lee at Gettysburg -- 8. 1895: Knowing Your Country's Place in the World; Lord Salisbury Saves the British Empire -- 9. 1898-1912: The Promised Land Fallacy; Von Tirpitz Disastrously Builds a Navy -- 10. 1970: Knowing the Nature of the World You Live In; Or the Trials and Tribulations of George Harrison -- 11. 1978: The Butterfly Effect in Political Risk; Or Deng Xiaoping and the Perils of a Drunken Sea Captain -- 12. Conclusion: Back to the Pythia's Lair; Mastering Geopolitical Risk.
Includes bibliographical references (pages [307]-311) and index.
Keywords: World history; World politics